2013
DOI: 10.1063/1.4798828
|View full text |Cite
|
Sign up to set email alerts
|

Non-conducting interfaces of LaAlO3/SrTiO3 produced in sputter deposition: The role of stoichiometry

Abstract: (001) oriented L10 FePt/B4C multilayer thin films on naturally oxidized Si substrate J. Appl. Phys. 113, 17C108 (2013) Multiple oxide content media for columnar grain growth in L10 FePt thin films Appl. Phys. Lett. 102, 112411 (2013) Magnetic and high frequency properties of nanogranular CoFe-TiO2 films J. Appl. Phys. 113, 17A316 (2013) Low substrate temperature fabrication of high-performance metal oxide thin-film by magnetron sputtering with target self-heating Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…This measurement further supports the result that La/Alr0.97 ± 0.03 is a necessary condition for obtaining a 2-DEL at La ( 3 interfaces and suggests that this result is independent of the growth method used as long as the growth conditions do not promote extrinsic defects. The non-conducting interfaces reported in sputtered films that are found to be La-rich 35 is also consistent with our result (see Supplementary Note 2).…”
Section: Mosaic Growth Experimentsupporting
confidence: 82%
“…This measurement further supports the result that La/Alr0.97 ± 0.03 is a necessary condition for obtaining a 2-DEL at La ( 3 interfaces and suggests that this result is independent of the growth method used as long as the growth conditions do not promote extrinsic defects. The non-conducting interfaces reported in sputtered films that are found to be La-rich 35 is also consistent with our result (see Supplementary Note 2).…”
Section: Mosaic Growth Experimentsupporting
confidence: 82%
“…The resulting interface conductance strongly depends on the oxygen pressure, 1,5 indicating that the formation of oxygen vacancies plays a role in the conductance as well. This is also found in experiments involving sputter deposition, 6 or post-annealing. 7 In view of the influence of the termination layer, the atomic structure of the starting surface is of obvious importance; however, relatively little research has been done to clarify this at actual growth conditions, which entail both a high temperature and a certain oxygen pressure.…”
supporting
confidence: 52%
“…Recent observations have also indicated that the cationic stoichiometry, e.g., the La/Al ratio in LaAlO3 film, may affect the electrical properties of LaAlO3/SrTiO3 18,48,49 shows the atomically flat surface with unit cell steps. The growth target was LaAlO3 single crystal, also obtained from Crystec.…”
Section: /33mentioning
confidence: 99%